Moult as a dynamic link in the annual cycle of birds: insights from seabirds and a long-distance migratory raptor - Adekola, Oluwadunsin E (Department of Biological Sciences, 2023)
Moult is one of three major and costly events in the annual cycle of birds, alongside breeding and migration. Unlike breeding and migration, moult is indispensable, and its patterns vary considerably among species. Despite the importance of moult, it has been relatively less studied than breeding or migration. Moult can evolve rapidly in response to environmental changes and may make substantial demands on endogenous metabolism. Moult represents perhaps the single highest cost of maintenance for birds and requires a major allocation of resources. The study of moult has important consequences for understanding bird biology and conservation. Knowledge of moult is central to understanding life-history trade-offs in birds and to predict the consequences of global change. To date, most moult studies mainly focus on primaries, but it is important to understand other feather tracts, such as the secondaries, which can exceed primaries in number, total length and mass in long-winged birds. Feather replacement is more challenging for large birds than small birds, due to the time required to grow their long wing feathers. In this thesis, I explore how different birds balance moult with other aspects of their annual cycles. In particular, I assess how large, long-winged birds manage to replace their large number of secondaries. I also explore whether nestlings grow flight feathers of equal quality as adults in a long-distance migratory raptor. The study of feather quality in birds is still in its infancy, but the few studies to date indicate that chicks compromise feather quality to minimise their nestling period. In addition, few studies have explored how moult strategies are influenced by differences in food availability or habitat quality. To explore these questions, I describe moult strategies in three seabird species (Cape Gannet Morus capensis, White-chinned Petrel Procellaria aequinoctialis and Whitecapped/Shy Albatrosses Thalassarche steadi/cauta) and a long-distant migratory raptor (Amur Falcon Falco amurensis). My choice of study species was driven principally by the large data sets available for them. I also explore structural variations of flight feathers and primary coverts in 100 non-moulting Amur Falcons. There are seven chapters including an introductory first chapter. In Chapter 1, I introduce the importance of feathers and why maintaining their quality is key to birds' survival. Feathers are dead structures once formed, and have to be replaced regularly. However, this replacement is costly. Using relevant literature, I summarize moult in seabirds and raptors. I also give the rationale, knowledge contribution and outline of the thesis. In Chapter 2, I compare the structure of flight feathers and primary coverts of non-moulting Amur Falcons of known age and sex. Adults had longer and relatively heavier feathers than juveniles, but other microstructural measurements did not differ between ages or sexes. Adults and juveniles had similar calamus length across primaries, secondaries, rectrices and primary coverts. However, juvenile primaries, secondaries and rectrices had a shorter rachis than adults. There were no age-related differences among primary coverts. There were no age related differences among primary coverts. Body condition was higher in females than males in both adults and juveniles. In general, adults and juveniles with better body condition tended to have longer and heavier feathers, with limited variations across feather tracts, suggesting that feather traits could be used as reliable indicators of a bird's health. Contrary to previous studies that growing feathers fast reduces their quality, my results suggest that juvenile Amur Falcons manage to grow quality flight feathers in terms of microstructure even though they fledge in about one month, and they do not appear to wear faster than adult flight feathers. In Chapter 3, I show that moult duration and symmetry, but not timing, differ between two breeding colonies of Cape Gannets in South Africa. My results suggest that moult may be used as an index of condition. Primary moult is protracted, with multiple active centres and up to five primaries growing at the same time. Secondary moult commences after primary moult has started and proceeds from two nodal points, growing more feathers simultaneously than primaries. Tail moult also overlaps with that of the primaries, with multiple active centres and up to eight rectrices growing at once. I suggest that differences in moult duration and perhaps asymmetry between breeding colonies may be linked to foraging conditions, given that gannets breeding at Lambert's Bay are under greater food stress than those breeding on Malgas Island. In Chapter 4, I describe patterns of wing and tail moult in White-chinned Petrels and assess whether flight activity is reduced during the period of most intense wing moult. White-chinned Petrels exhibit a simple descendent primary moult, with age- and sex-related differences in the timing of moult. Secondary moult is extensive and commenced after 3–4 primaries had been dropped, typically progressing from three nodal sites. Photographs of non-moulting birds at sea confirm that some White-chinned Petrels do not replace all secondaries each year. Tail moult usually commences with the start of secondary moult and is highly variable, with 1–12 rectrices growing at once. Unlike many smaller petrels, there is little evidence that adults reduce the time spent flying while moulting, despite the intense nature of wing and tail moult. In Chapter 5, I show that despite being on their non-breeding grounds, there was low proportion of moulting White-capped/Shy Albatrosses. Although a few birds exhibited intense moult, replacing up to six primaries and 14 secondaries at once, the norm was for replacing only 1-2 primaries (mean ± SD, 1.9 ± 1.2), and 2-6 secondaries (3.9 ± 3.0) at once, which is surprising given the expectation that large, long-winged birds should be under time pressure to complete their moults. This occurs as adults typically take a year off between successful breeding attempts, seemingly allowing time for a more protracted moult. Secondary moult overlaps with primary moult and progresses from three nodal sites: first dropping the innermost five to eight secondaries, followed by the outermost four secondaries and almost simultaneously with S16–S22 and S4–S7, ending with the middle secondaries (although not all moulted each year). Tail moult commences at the start of primary moult, with multiple active centres (2.7 ± 1.6; 1–6) and 3.8 ± 2.9 feathers growing at the same time (range 1–11). Most birds replaced their rectrices in pairs, starting from the central feathers, but some birds replaced alternate feathers, or replaced almost all rectrices at once. Age and sex differences in moult intensity may be due to time constraints. The low proportion of moulting birds on their non-breeding grounds might suggests that moult in White-capped Albatrosses is more constrained during the non-breeding period in southern African waters. In Chapter 6, I present the results of extent and symmetry of moult in a long-distance migratory raptor, the Amur Falcon, killed by hailstorms at its roosts in South Africa during March. By this time of year, most adults have completed replacing their remiges, with only a few still growing 1–3 feathers (mainly secondaries), but most are still growing their tail feathers. Moult typically is distal from the central rectrices, but 25% of adults and 1% of juveniles replace the outer tail first, and a few individuals exhibit other moult patterns (simultaneous moult across the tail, or among the inner and outer feathers). These different moult strategies are independent of sex. Adults that replace the outer tail first typically have replaced a greater proportion of the rectrices than adults starting from the central tail. The extent of tail moult is correlated with body condition in adults and juveniles, suggesting that moult pattern might be used as an indicator of fitness in falcons. Finally, in the thesis synthesis (Chapter 7), I summarise the main results from the previous chapters. I also explore the relative impact of secondary moult in terms of loss of wing area in 102 bird species, ranging from small passerines to seabirds, raptors, waterfowl and other large birds. I measure the proportion of total wing area accounted for by the secondaries projecting beyond the greater secondary coverts across the different bird species to show that seabirds (apart from cormorants, Phalacrocoracidae) have less secondary area than most other groups of birds. I also show that secondary wing area is less in long-winged birds. The significant positive correlation between proportion of secondary area and body mass indicates that secondary area scales allometrically. I propose that the relatively small secondary area not covered by greater coverts in long-winged seabirds allows these species to replace large numbers of secondaries at once. At least in petrels and some gulls, this adaptation is facilitated by the near-simultaneous replacement of most greater secondary coverts at the start of primary moult, so the secondary coverts are already replaced once secondary moult starts.